Investigating quorum-quenching marine bacilli as potential biocontrol agents for protection of shrimps against Early Mortality Syndrome (EMS) - Moritz, Müller; Andrew J., Spiers; Angelica, Tan; Aazani, Mujahid (Springer Nature Limited, 2023)
Early Mortality Syndrome (EMS) has been a major problem for shrimp aquaculture in Southeast Asia due to its epizootic prevalence within the region since the first reported case in 2009. This study explores the application of halophilic marine bacilli isolated from coral mucus and their quorum-quenching abilities as potential biocontrol agents in aquaculture systems to combat the causative agent of EMS, Vibrio parahaemolyticus. N-acylhomoserine lactone (AHL)-degrading (AiiA) activity was first screened by PCR then confirmed by bio-reporter assay, and a combination of 16S rDNA sequence analysis and quantitative phenotype assays including biofilm-formation and temperature-growth responses were used to demonstrate diversity amongst these quorum-quenching isolates. Three phenotypically distinct strains showing notable potential were chosen to undergo co-cultivation as a method for strain improvement via long term exposure to the pathogenic V. parahaemolyticus. The novel approach taken led to significant improvements in antagonism and quorum quenching activities as compared to the ancestral wild-type strains and offers a potential solution as well as pathway to improve existing beneficial microbes for one of the most pressing issues in shrimp aquacultures worldwide.